COVID-19 impact on liver: inter-organ cross-talk in an acute inflammation - Yadav, Dipesh Kumar; Singh, Alina; Yadav, Rajesh Kumar; Xing, Huang; Li, Bai Xue; Tingbo, Liang (Journal of Patan Academy of Health Sciences, 2021)
Since coronavirus disease 2019 (COVID-19) has been a new disease, very less is known about the disease, and guidance for the treatment are often being made on the basis of an experiences or expert opinions. Now it is known that COVID-19 is caused by a new Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus which elicit infection to the cells by binding of the spike protein to angiotensin converting enzyme 2 (ACE2). Given the high transmissibility rate of the SARS-Cov-2 virus and known to have cytokine dysregulation by inducing an immune-mediated systemic inﬂammation, patients with underlying liver disease might be at an increased risk of severe infection and death. Here we report different mechanisms based on the organ cross-talk and other causes that how COVID-19 patients are prone to have liver injury.